FENOMENA KEJUT BUDAYA (CULTURE SHOCK) PADA MAHASISWA RANTAUAN DI FISIP UNIVERSITAS UDAYANA - Mulya Astari, Gusti Ayu Agung Chandra; Zuryani, Nazrina; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT Most of student at FISIP Unud are students migrants. This research took two problem formulations; how is the culture shock phenomenon experienced by the students migrants at the Faculty of Social and Political Sciences, Udayana University and how the students migrants overcome cultural shock in their new environment. The theory in this study is the thought of an anthropologist Kalvero Oberg in the 1960s. The result from the research that the students migrants experienced culture shock by several factor, such as: sosio-cultural factors, environmental factors, culinary and tourism factors and homesickness. There are several ways to overcome the cultural shock that are done by the students migrants which is different onto each other’s according to the personality of each individual e.i: adapting local communication through language adjustment the way locals communicate, learn and try to fit in the new culture, follow which happened to be popular in their new environment. Keywords: Culture Shock, Student Migrants, Crisis Cultural.